2020
DOI: 10.1061/(asce)co.1943-7862.0001748
|View full text |Cite
|
Sign up to set email alerts
|

Critical Strategies for Enhancing BIM Implementation in AEC Projects: Perspectives from Chinese Practitioners

Abstract: This material may be downloaded for personal use only. Any other use requires prior permission of the American Society of Civil Engineers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 72 publications
2
49
1
4
Order By: Relevance
“…This component is composed of the following four attributes: "software availability issues", "inadequate contractual coordination", "data and intellectual property issues", and "technological availability issues" with factor loadings of 0.741, 0.735, 0.690 and 0.507 respectively. The high cost (hence availability) associated with the variable of technological availability issues has been attributed to as one of the major challenges or barriers to BIM implementation not in in Nigeria (Saka and Chan, 2019a), but other developing countries such as China (Ma et al, 2020); and Malaysia (Enegbuma et al, 2014). For instance, the study by (Saka and Chan, 2019a) described BIM as technologically oriented process, thus bringing to the fore the importance around the issues of software and technological availability.…”
Section: Component 1: Technology and Business-related Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…This component is composed of the following four attributes: "software availability issues", "inadequate contractual coordination", "data and intellectual property issues", and "technological availability issues" with factor loadings of 0.741, 0.735, 0.690 and 0.507 respectively. The high cost (hence availability) associated with the variable of technological availability issues has been attributed to as one of the major challenges or barriers to BIM implementation not in in Nigeria (Saka and Chan, 2019a), but other developing countries such as China (Ma et al, 2020); and Malaysia (Enegbuma et al, 2014). For instance, the study by (Saka and Chan, 2019a) described BIM as technologically oriented process, thus bringing to the fore the importance around the issues of software and technological availability.…”
Section: Component 1: Technology and Business-related Barriermentioning
confidence: 99%
“…Most importantly, the lack of collaboration knowledge, skills and abilities led to insufficient understanding of the BIM process, and hence interoperability issues (Oraee et al, 2019). More so, capabilities and skills in BIM technology are acknowledged among the strategies for enhancing BIM implementation (Ma et al, 2020). Similarly, in Iran which is a developing country like Nigeria, Marefat et al (2019) identified lack of well-trained personnel among the factors that lead to failure in the adoption of BIM.…”
Section: Component 2: Training and People-related Barriermentioning
confidence: 99%
“…Prior studies emphasized BIM adoption frameworks from different categorical aspects. For instance, in organizational level, studies stressed the impact of financial capacity, practice, and readiness of major construction firms on the integration of BIM in organizational structures [5,15], whereas in project and industry levels, they highlighted (1) barriers and benefits of BIM adoption and diffusion in the construction industry [16], (2) diffusion challenges associated with BIM implementation [17], and (3) critical strategies of BIM adoption across different markets [18].…”
Section: Introductionmentioning
confidence: 99%
“…A 5-point Likert scale, ranging from 1 � not critical, 2 � not quite critical, 3 � fairly critical, 4 � very critical, and 5 � extremely critical, was adopted in this study to get the perception of professionals who consisted of clients, consultants, contractors, and academia and are currently working in public construction projects across Ethiopia. Prior studies suggest that a 5-point Likert scale has been proven to be useful for a reliable data analysis in similar investigations around the world [41,44]. e draft questionnaire then was sent to four experienced professionals (2 in academia and 2 in the industry) for content validation.…”
Section: Data Collectionmentioning
confidence: 99%